2012
DOI: 10.1038/msb.2012.9
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell analysis of population context advances RNAi screening at multiple levels

Abstract: A large set of high-content RNAi screens investigating mammalian virus infection and multiple cellular activities is analysed to reveal the impact of population context on phenotypic variability and to identify indirect RNAi effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
139
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 158 publications
(143 citation statements)
references
References 53 publications
4
139
0
Order By: Relevance
“…Therefore, viral entry pathways can be described only for a particular cell line, and general concepts can be obtained only after testing several host factors (75). This notion is also supported by a small RNAi screen targeting 50 protein kinases that has shown that HSV-1 gene expression relies on different kinases in the HeLaKyoto or HeLaMZ cell lines (36).…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, viral entry pathways can be described only for a particular cell line, and general concepts can be obtained only after testing several host factors (75). This notion is also supported by a small RNAi screen targeting 50 protein kinases that has shown that HSV-1 gene expression relies on different kinases in the HeLaKyoto or HeLaMZ cell lines (36).…”
Section: Discussionmentioning
confidence: 90%
“…HeLa cells were from the ATCC. HeLa Kyoto cells were a kind gift from L. Pelkmans (Institute of Molecular Life Sciences, Zurich, Switzerland) (34). HaCaT cells that originated from N. Fusenig (DKFZ, Heidelberg, Germany) (35) were a kind gift from the Schiller lab (NIH, National Cancer Institute, Bethesda, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
“…We find that seed effects are also present in published largescale RNAi datasets that have been corrected for indirect effects occurring through changes in a single cell's microenvironment (27,28) ("population context") (Fig. S7).…”
Section: Discussionmentioning
confidence: 74%